The Success Story of UMPSA-BJTU Dual Degree Programs - Ahmad Ziad, Sulaiman; Lee, Khai Loon (UMPSA, 2025)
Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and Beijing Jiaotong University (BJTU), China, have established a groundbreaking partnership through a Memorandum of Agreement (MoA) signed on April 28, 2021.